P-160 Community palliative care specialist nurse 7-day service: does it make a difference?. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Blakey, Claire; Jones, Jane
Abstract : Background: The Community Palliative Care Specialist Nurse (PCSN) team identified challenges faced out of hours (OOH), for patients, carers and health care professionals (HCP) with reported experiences of poor symptom management, carer distress and absence of specialist palliative care (SPC) support and advice. These observations supported the Parliamentary and Health Service Ombudsman report (2015), that patients and carers 'suffered' due to difficulties accessing SPC OOH, concluding that; 'for the benefit of their comfort, dignity and wellbeing, all in need should have access to SPC services whenever they need it'. In response, the PCSN team implemented a service extension to seven days a week. Aim: To evaluate the PCSN service extension, explore outcomes and interventions, and evaluate patients', carers', HCPs' and PCSN team experiences. Method: The evaluation included analysis from a workshop review, staff focus groups, patient, carer and HCP feedback, data collection and analysis of activity and outcome data. Results: The following themes emerged from the evaluation analysis; Improved symptom management – timely, proactive interventions and face-to-face assessments, with a focus on utilising specialist skills for patients in the unstable phase of illness (Witt, de Wolf-Linder, Dawkins et al ., 2013). Interventions contributed to reduced medication errors. Place of care – patients remained at home, acute admissions avoided and appropriate hospice or hospital admissions facilitated. Collaborative team work – improved external and internal working relationships. Improved experience – feedback indicated feelings of reassurance, support and reduced anxiety. Conclusion: The evaluation has demonstrated improved patient, carer and HCP outcomes and experiences through access to a seven-day PCSN service. Additionally, evaluation supports national directives on access to seven-day SPC services as essential and offers experience into the challenges of delivering this within the community. Research is planned to further explore the effectiveness of PCSN interventions in improving patient outcomes.